Analisis Penerapan PSAK 1 pada Laporan Keuangan Perusahaan Rokok yang Terdaftar di BEI Tahun 2019-2021 - Dian Widiana; Waluya Waluya; Sri Maria Ulfha (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2023)
This study aims to determine how the application of PSAK 1 regarding the presentation of financial statements in cigarette companies listed on the Indonesia Stock Exchange (IDX) qualitative data analysis research techniques and obtaining documentation data. The required data collection is secondary data obtained from the IDX web, namely www.idx.co.id and there are 5 cigarette sub-sector companies, the data had taken are annual financial statements for three periods that have been audited. This study begins with a comparative analysis of research subjects with a comparative concept in terms of accounting policies and presentation of financial statements, then tries to adjust and compare two elements, namely PSAK 1 on the presentation of financial statements and financial statements of cigarette companies listed on the Indonesia Stock Exchange (IDX). The results of this study are that there are 2 cigarette companies listed on the Indonesia Stock Exchange that have not fully implemented PSAK 1 in the presentation of their financial statements, there are several components that in practice are not in accordance with PSAK 1.Keywords: Financial Statements, Presentation of Financial Statements, PSAK 1